PENGELOLAAN DESA WISATA DAN DAMPAK TERHADAP EKONOMI, SOSIAL DAN BUDAYA (KAJIAN DI DESA PINGE – TABANAN) - I Wayan Pantiyasa; Ni Luh Supartini (Jurnal Ilmiah Hospitality Management, 2015)
Community based Tourism paradigm as a concept of alternative tourism has been able to provide generalization to community prosperity or development towards sustainable tourism. In relation to this paradigm, this study was conducted to analyze the management system in Pinge village in terms of operational, marketing, community participant and the impacts of rural tourism development in Pinge village. The approach used in this research was qualitative descriptive. Techniques of collecting data were through interviewing with community leaders and conducting field observations. From the result of study, it was found that the management of Pinge village has strengthens such as a good package of tourism products, a good relationship between travel agents, government and good support from the community. Furthermore, the weaknesses are the lack of promotion media and limited of professional human resources. The result of this study is expected as a reference study in rural tourism development in Pinge village through controlling the negative impacts from this tourism destination development.